Unlocking Dead Capital - Safavian, Mehnaz (World Bank, Washington, DC, 2012)
Collateral can increase access to finance, especially for small firms, and lead to better terms for loan contracts. Many argue that firms are excluded from formal credit markets because they lack assets that can serve as collateral. In fact, firms generally have a wide array of productive assets that could secure a loan-but the legal framework prevents this. Reforming collateral laws can unlock dead capital, as seen in Albania and Romania.